Cement-free algae mud plate and preparation method thereof
Through the design of cementless algae mud sheets and high-temperature and high-pressure autoclave curing treatment, the existing diatom mud sheets have been solved, and the board density is reduced, structural strength maintenance and durability are improved, and it is suitable for the field of building decoration.
Patent Information
- Application Number
- CN202411852311.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing diatom mud sheets have high density and are not suitable for industrial production and finish review. They have high labor and physical strength requirements, low yield rate, and cement addition will lead to ablation of the finish, and the small content of diatom mud affects the purification efficiency.
The cementless algae mud plate is made of pulp, diatomaceous earth, quartz sand, slurry lime, wollastonite, metal elements and rock stone. Tobemolite crystals are generated through high-temperature and high-pressure autoclave maintenance treatment to improve the durability and stability of the material.
It achieves the reduction of the plate density and maintains structural strength, avoids the damage of cement components to the finishing materials, reduces carbon emissions, reduces material weight and cost, and improves the durability and sound insulation of the material.
Smart Images

Figure CN119661171A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of boards, and in particular relates to a cement-free algae mud board and a preparation method thereof. Background Art
[0002] Diatom mud is a very well-known healthy decorative material. The material itself is non-toxic and harmless. Currently, it is mainly used in the field of architectural decoration as diatom mud paint, which is used by applying it on the wall. Although some of the health characteristics of the material have been responded to, its finishing effect has not been broken through.
[0003] The density of existing diatom mud boards is generally greater than 1.2, which is not conducive to industrial production, finishing review and on-site installation. It requires extremely high physical strength of the labor force and has a low yield rate. The addition of cement in the board will cause alkali erosion of the finish when it encounters moisture. More specifically, the content of diatom mud is relatively low (generally around 15%), so the purification efficiency and capacity are greatly reduced. Also, due to its heavy specific gravity, it cannot be used in ceilings and other scenarios. Summary of the invention
[0004] The object of the present invention is to provide a cement-free algae mud board and a preparation method thereof to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A cement-free algae mud board, composed of the following materials in parts by weight:
[0007] Pulp (short fiber) 6-8%, pulp (medium and long fiber) 2.5-3.5%, diatomaceous earth 32-38%, quartz sand 24-28%, slaked lime 18-22%, wollastonite 5-7%, metal elements 2.5-3.5%, rod stone 0.5-1% and pure water, wherein the pure water is added to the pulping concentration of 10-12%.
[0008] Preferably, the diatomaceous earth has a silicon content of not less than 85%;
[0009] The mesh number of the quartz sand is 300-400 mesh;
[0010] The pulp has a beating degree of 45-55 and a wet weight of 8-12;
[0011] The calcium hydroxide content of the slaked lime is more than 90%, and the mesh size is 200-300 mesh;
[0012] The metal element is one or more of iron, zinc, titanium and nickel.
[0013] A method for preparing a cement-free algae mud board comprises the following steps:
[0014] S1. Pump the pulp (short fibers and medium and long fibers) into a pulper, add quartz sand, diatomaceous earth, slaked lime, and finally add the remaining materials, and stir thoroughly to form a slurry;
[0015] S2, sending the slurry into the slurry storage tank, quantitatively and evenly supplying the pulping machine for further mixing, and then sending it into the premixing tank for premixing treatment, detecting the mass concentration of the slurry and adjusting the flow rate;
[0016] S3, the slurry flows out evenly through the headbox and is spread on the running industrial conveyor belt, the water is filtered out by the vacuum system, and a thin layer of material is wrapped around the forming cylinder. When the set thickness of the blank is reached through multiple layers of wrapping, the blank is cut off, the scraps are removed, and the blank is transported to the blank receiving machine. A stacker is used to stack one template and one slab alternately;
[0017] S4, after the wet slabs are stacked, they are pre-cured to make the slabs reach the initial strength, and the pre-cured slabs are sent to the demoulding machine for demoulding and stacking;
[0018] S5, the demoulded slab is pulled into the autoclave through the slab stack on the steaming car by a traction machine for autoclave maintenance, and the silicon dioxide, calcium hydroxide and water in the slab undergo hydration reaction under high temperature and high pressure to finally generate tobermorite crystals;
[0019] The autoclave process includes heating, constant temperature, and cooling, and the constant pressure is 1.0-1.5MPa;
[0020] S6. The steamed slab is continuously dried by a dryer to reduce the moisture content of the slab to below 9.5%;
[0021] The board stack trolley with the steam-cured pads coming out of the autoclave is separated from the boards and the steam-cured pads by a board suction machine;
[0022] The boards discharged from the dryer are discharged and stacked through the board-discharging belt conveyor, the positioning roller conveyor and the vacuum board suction machine;
[0023] S7. The dried slab is subjected to a double-sided sanding machine to determine its thickness, and then the slab edge is ground and chamfered by an edge grinding and chamfering unit.
[0024] Preferably, in S4, the pre-curing time is 12-24 hours.
[0025] Preferably, in S5, the autoclave curing includes heating for 2-3 hours, maintaining the temperature for 8-12 hours, and cooling for 2-4 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) By not adding cement, the structural strength of the board is not affected, and the damage to the later finishing materials caused by certain components in the cement is avoided. The carbon emissions in the production process are reduced, and the weight and cost of the material itself are also reduced.
[0028] (2) The cement-free algae mud board undergoes high temperature and high pressure autoclaving and curing treatment to generate stable tobermorite crystals, thereby improving the durability and stability of the material. It is not easy to deform or crack during use and can maintain a long-term sound insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] See also Figure 1 As shown, a cement-free algae mud board is composed of the following materials in parts by weight:
[0033] Pulp (short fiber) 7%, pulp (medium and long fiber) 3%, diatomaceous earth 35%, quartz sand 26%, slaked lime 20%, wollastonite 5.81%, metal elements 3%, rod stone 0.75% and pure water. Pure water is added to the pulping concentration of 11%.
[0034] In one embodiment of the present invention, the silicon content of diatomaceous earth is not less than 85%; the mesh size of quartz sand is 350 meshes; the beating degree of pulp is 50, and the wet weight is 10; the calcium hydroxide content of slaked lime is more than 90%, the mesh size is 250 meshes, and the metal element is one or more of iron, zinc, titanium, and nickel.
[0035] A method for preparing a cement-free algae mud board comprises the following steps:
[0036] S1. Pump the fiber material into the pulper, then add quartz sand, diatomaceous earth, slaked lime and other materials, and finally add auxiliary materials to improve the function, fully mix the powdered material and pulp in the mixer to make slurry, and send it to the slurry storage tank for standby;
[0037] S2. The slurry in the slurry storage tank is quantitatively and evenly supplied to the double-disc refiner by a pump to further mix the slurry, and then sent to the slurry storage machine for storage and standby use. The ground slurry is then sent from the slurry storage machine to the set weighing, concentration, and other technical requirements for pre-mixing and stirring. The mass concentration of the slurry can be detected and the flow rate can be adjusted;
[0038] Constant slurry concentration can stabilize the operation of the slurry flow board making machine and facilitate the adjustment of board thickness;
[0039] S3, the slurry flows out evenly through the headbox and is spread on the running industrial conveyor belt, the water is filtered out by the vacuum system, and a thin layer of material is wrapped around the forming cylinder. When the set thickness of the blank is reached through multiple layers of wrapping, the blank is cut off, the scraps are removed, and the blank is transported to the blank receiving machine. A stacker is used to stack one template and one slab alternately;
[0040] The plate making machine uses a forming cylinder of a certain diameter, and after the blank is unloaded, it is cut and made into a slab with a specification larger than the standard (standard slab: 1220mmx2440mm);
[0041] The stacker uses a servo motor, which can precisely control the speed and positioning accuracy;
[0042] The height of the maintenance trolley and the template trolley is automatically adjusted by two elevators, and the entire process of plate making, blank connection and stacking is automatically controlled;
[0043] S4, after the wet slabs are stacked, they are pre-cured to make the slabs reach the initial strength, and the pre-cured slabs are sent to the demoulding machine for demoulding and stacking;
[0044] S5, the demoulded slab is pulled into the autoclave through the slab stack on the steaming car by a traction machine for autoclave maintenance, and the silicon dioxide, calcium hydroxide and water in the slab undergo hydration reaction under high temperature and high pressure to finally generate tobermorite crystals;
[0045] The stripped template is cleaned and oiled by a dust cleaning and oiling machine, then stacked on a trolley and returned to the stacker along the track for recycling. The slab is then ferried to the front of the autoclave by a ferry car and assembled into the autoclave;
[0046] After the slab enters the autoclave, it needs to be subjected to high temperature and high pressure for about 10 to 26 hours;
[0047] The autoclave process includes heating, constant temperature, and cooling. The constant pressure is 1.0-1.5MPa. The autoclave criteria are: heating for 2 hours, constant temperature for 8-10 hours, cooling for 3-4 hours, and constant pressure of 1.28MPa.
[0048] Before autoclaving, the kettle needs to be evacuated to -0.48 atmospheres, which is more conducive to saving steam, making the algae mud board absorb heat evenly and have good air permeability, so as not to cause the disadvantages of autoclaving;
[0049] S6. The steamed slab is continuously dried by a dryer to reduce the moisture content of the slab to below 9.5%;
[0050] The slabs are dried continuously in the tunnel kiln through the dryer, and the hot air is circulated in the kiln by the axial flow fan, so that the slabs are dried evenly;
[0051] The board stack trolley with the steam-cured pads coming out of the autoclave is separated from the boards and the steam-cured pads by a board suction machine;
[0052] The boards discharged from the dryer are unloaded and stacked through the board-discharging belt conveyor, positioning roller conveyor and vacuum board suction machine, and then transported to the semi-finished product storage area by forklift;
[0053] S7. To ensure the flatness of the board surface, sanding and edge grinding are used to enhance the appearance quality. The dried slab needs to be thickness-determined by a double-sided sander. The sanded board is then ground and chamfered by an edge grinding and chamfering unit.
[0054] In one embodiment of the present invention, in S4, the pre-curing time is 12-24 hours.
[0055] In one embodiment of the present invention, in S5, the autoclave curing includes heating for 2-3 hours, maintaining the temperature for 8-12 hours, and cooling for 2-4 hours.
[0056] Embodiment 2:
[0057] The difference from Example 1 is that a cement-free algae mud board is composed of the following materials in parts by weight: 6% pulp (short fiber), 2.5% pulp (medium and long fiber), 32% diatomaceous earth, 24% quartz sand, 18% slaked lime, 5% wollastonite, 2.5% metal elements, 0.5% rod stone and pure water. The pure water is added to the pulping concentration of 10%. The rest is the same as Example 1 and will not be repeated here.
[0058] Embodiment three:
[0059] The difference from Example 1 is that a cement-free algae mud board is composed of the following materials in parts by weight: 8% pulp (short fiber), 3.5% pulp (medium and long fiber), 38% diatomaceous earth, 28% quartz sand, 22% slaked lime, 7% wollastonite, 3.5% metal elements, 1% rod stone and pure water. The pure water is added to the pulping concentration of 12%. The rest is the same as Example 1 and will not be repeated here.
[0060] Application test case
[0061] Flammability test:
[0062] Take the algae mud board in Example 1 and conduct a combustion performance A (A1) test on it, including single test items such as temperature rise in the furnace, mass loss rate, continuous burning time and total calorific value, as shown in the following table:
[0063]
[0064] After testing, the algae mud board sample provided in the embodiment of the present invention meets the technical requirements of Class A (A1) non-combustible materials (products) in GB8624-2012 "Classification of Combustion Performance of Building Materials and Products", indicating that it has excellent combustion performance.
[0065] Product ingredient testing:
[0066] The algae mud board in Example 1 was used for product testing, as shown in the following table:
[0067]
[0068]
[0069] Among them, formaldehyde purification efficiency test: the experimental sample size is 1m 2 ; Sealed cabin volume: 1m 3 , sample size: 1m 2 , Experimental conditions: temperature (25+1)℃, relative humidity (50+10)%, samples were tested as W-type non-photocatalytic materials (without turning on the light, 24h);
[0070] Description of non-detection: Formaldehyde emission <0.10mg / L; Hexavalent chromium content <1mg / kg; Cadmium content <5mg / kg: Mercury content <5mg / kg.
[0071] Acoustic performance testing:
[0072] This test is conducted in accordance with GB / T19889.3-2005 "Acoustic buildings and building components sound insulation measurement Part 3: Laboratory measurement of airborne sound insulation of building components" and GB / T20247-2006 "Acoustic reverberation chamber sound absorption measurement". The test items mainly include sound insulation and sound absorption coefficient. The test environment is controlled within the range of temperature 20-25℃ and humidity 50-60%RH to ensure the accuracy and comparability of the test results, as shown in the following table:
[0073]
[0074]
[0075] After testing, the sound insulation result of the algae mud board was 52dB, exceeding the 30-50dB range of the test index and was judged to be qualified; the sound absorption coefficient test result was 0.91, exceeding the 0.5-0.8 range of the test index and was also judged to be qualified.
[0076] By removing cement as the main unfavorable material for structural condensation, the addition amount of diatom mud is increased to 35%, and the density is as low as 0.5-0.9. The efficiency and ability of purifying formaldehyde and volatile organic compounds are (more than 97% purification level is completed within 2-6 hours), which is dozens of times higher than the negative ion release level under relative conditions, and the sound insulation and sound absorption capabilities reach 52 decibels and 0.91 sound absorption efficiency; the energy storage effect is also very obvious, and the energy-saving level is particularly prominent compared with other materials. It is also a benchmark product in carbon emissions and carbon neutrality in the field of building materials; the composite of other finishing materials does not require penetration crystallization treatment, and will not have a negative impact on the adsorption performance of diatom mud; the water absorption level can reach more than 60%, and the water storage and indoor humidity balance effects are very good, which also plays a positive role in the stimulation of indoor negative oxygen ions and complements each other; the lightweight mass density is adapted to the application of all fields of building decoration, reduces the physical energy consumption of the labor force, and has a more positive significance for the health of workers.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A cement-free algae mud board, characterized in that: It is composed of the following materials by weight: Pulp (short fiber) 6-8%, pulp (medium and long fiber) 2.5-3.5%, diatomaceous earth 32-38%, quartz sand 24-28%, slaked lime 18-22%, wollastonite 5-7%, metal elements 2.5-3.5%, rod stone 0.5-1% and pure water, wherein the pure water is added to the pulping concentration of 10-12%.
2. The cement-free algae mud board according to claim 1, characterized in that: The silicon content of the diatomaceous earth is not less than 85%; The mesh number of the quartz sand is 300-400 mesh; The pulp has a beating degree of 45-55 and a wet weight of 8-12; The calcium hydroxide content of the slaked lime is more than 90%, and the mesh size is 200-300 mesh; The metal element is one or more of iron, zinc, titanium and nickel.
3. A method for preparing a cement-free algae mud board, characterized in that: The following steps are involved: S1. Pump the pulp (short fibers and medium and long fibers) into a pulper, add quartz sand, diatomaceous earth, slaked lime, and finally add the remaining materials, and stir thoroughly to form a slurry; S2, sending the slurry into the slurry storage tank, quantitatively and evenly supplying the pulping machine for further mixing, and then sending it into the premixing tank for premixing treatment, detecting the mass concentration of the slurry and adjusting the flow rate; S3, the slurry flows out evenly through the headbox and is spread on the running industrial conveyor belt, the water is filtered out by the vacuum system, and a thin layer of material is wrapped around the forming cylinder. When the set thickness of the blank is reached through multiple layers of wrapping, the blank is cut off, the scraps are removed, and the blank is transported to the blank receiving machine. A stacker is used to stack one template and one slab alternately; S4, after the wet slabs are stacked, they are pre-cured to make the slabs reach the initial strength, and the pre-cured slabs are sent to the demoulding machine for demoulding and stacking; S5, the demoulded slab is pulled into the autoclave through the slab stack on the steaming car by a traction machine for autoclave maintenance, and the silicon dioxide, calcium hydroxide and water in the slab undergo hydration reaction under high temperature and high pressure to finally generate tobermorite crystals; The autoclave process includes heating, constant temperature, and cooling, and the constant pressure is 1.0-1.5MPa; S6. The steamed slab is continuously dried by a dryer to reduce the moisture content of the slab to below 9.5%; The board stack trolley with the steam-cured pads coming out of the autoclave is separated from the boards and the steam-cured pads by a board suction machine; The boards discharged from the dryer are discharged and stacked through the board-discharging belt conveyor, the positioning roller conveyor and the vacuum board suction machine; S7. The dried slab is subjected to a double-sided sanding machine to determine its thickness, and then the slab edge is ground and chamfered by an edge grinding and chamfering unit.
4. The method for preparing a cement-free algae mud board according to claim 3, characterized in that: In S4, the pre-curing time is 12-24 hours.
5. The method for preparing a cement-free algae mud board according to claim 3, characterized in that: In S5, the autoclave curing includes heating for 2-3 hours, maintaining the temperature for 8-12 hours, and cooling for 2-4 hours.
Citation Information
Patent Citations
Production formula and preparation method of functional diatom ooze decoration material
CN103011739A
Diatom ooze wall material capable of efficiently purifying air or resisting against bacteria or automatically humidifying and preparation method of diatom ooze wall material
CN104446283A
Diatom plate and production method thereof
CN108439926A
Ecological health plate for purifying air and inducing negative ions
CN109928707A
Moisture-controlling construction material
JP2001130946A